Teacher’s Lesson Plan In Lesson Study Context In SMP Cokroaminoto Palopo - Rahmawati Upa; Hermini (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
Lesson Plan is one of the most important element in teaching. It is the teachers’ road map of what students need to learn and how it will be done effectively during the class time. Due to its importance, in this research, the researcher try to conduct a research relaed to the teachers’ lesson plan in Lesson Study in SMP Cokromnito Palopo. This research is itended to describe how the teacher’s lesson plan in SMP Cokroaminoto Palopo. This reseach was done trough Lesson Study activities so the lesson plan described is Lesson Study context. This research employed qualitative research and applied descriptive study. The teacher was choosen as the subject of this research was the English teacher of SMP Cokroaminoto Palopo. She taught seven grade and the researcher observed two cycles planning. The research instrument were direct observation, video recording and teacher’s lesson plan. After analyzing the research, then the researcher can conclude that there are some aspects can be found from the Lesson Plan after pnanning for two cycles. They are : the teacher plan to use cooperative learning method, Learning media (memo paper, word card, and LCD), Assessment (teacher assessment), Students’ seating arrangement (U shape).